Blood‐brain barrier permeability is increased in early Alzheimer's disease and correlates with brain microstructure. (20th December 2022) - Reas, Emilie T.; Tsiknia, Amaryllis A.; Banks, Sarah J.; Rostowsky, Kenneth A; Andrews, Murray; Brewer, James B.; Bolar, Divya S
Abstract: Background: Vascular dysfunction frequently accompanies Alzheimer's disease (AD), and its suspected contributions to AD pathogenesis may be partly mediated by disrupted blood‐brain barrier (BBB) function. Despite consistent evidence for increased BBB permeability in AD, it remains unclear whether BBB damage occurs in preclinical stages, when therapeutic interventions may be most effective. Furthermore, the relationship between BBB breakdown and microstructural neurodegenerative changes have not been well characterized. Method: Dynamic contrast‐enhanced MRI and restriction spectrum imaging (RSI) were conducted to measure BBB permeability and brain microstructure, respectively, among 24 cognitively normal controls and eight individuals with mild cognitive impairment or mild AD (aged 77±5 years, 41% women). Participants were enriched for AD risk, with 72% amyloid‐positive as determined by cerebrospinal fluid amyloid‐B42/40 and 50% APOE4 carriers. The volume transfer coefficient K trans, an estimate of vascular permeability, and RSI measures of restricted, hindered, and free water diffusion, were computed in the hippocampus, entorhinal cortex, and across all white matter. Differences in K trans were examined between impaired and control subjects, and between APOE4 carriers and non‐carriers. Correlations between K trans and brain microstructure were computed to examine associations between BBB permeability and microstructure. Analyses adjusted for age, sex, and education. Subgroup analyses were conducted within cognitively normal controls. Result: Entorhinal cortex K trans was higher for cognitively impaired subjects than controls. Higher K trans correlated with lower education, but was not associated with age, sex, amyloid‐B42/40, hypertension, or APOE genotype. Among controls, white matter K trans was higher for APOE4 carriers versus non‐carriers. K trans correlated with restricted, hindered, and free water diffusion in the hippocampus, entorhinal cortex, and white matter within controls in an APOE‐dependent manner. Results were essentially unchanged by adjustment for amyloid‐B42/40 or hypertension. Conclusion: BBB permeability increases in individuals with mild cognitive impairment and in cognitively normal individuals at elevated genetic risk for AD, independent of amyloid pathology. BBB breakdown is associated with microstructural abnormalities that may reflect cell loss or dystrophy, or neuroinflammation, in an APOE‐dependent manner. Our findings suggest that BBB breakdown may occur in early AD and promote neurodegeneration via APOE‐dependent avenues, warranting further examination of the mechanisms underlying AD‐related BBB compromise.